Influence of predecessors on species diversity of weeds in winter wheat crops in the Eastern Forest-Steppe of Ukraine - R. Hutianskyi; S. Popov; V. Zuza; N. Kuzmenko (Карантин і захист рослин)
Goal. Determine the species composition of weeds, their dominant role and establish the type and level of weediness of winter wheat crops by cultivation on black fallow, after peas for grain and winter wheat as forecrops in the Eastern Forest-Steppe of Ukraine.